THE IMPROVEMENT OF SMELTER OPERATIONAL RISK BY USING RISK MANAGEMENT SYSTEM CASE: PT SILO - Salim, Themy
Indonesia mineral and coal mining activities are regulated by the Law on Mineral and Coal Mining No. 4 of 2009. One of the important points in new Mining Law is the increasing mineral value added through domestic processing & refining activities. PT Silo is an iron ore mining company that transformed itself into smelter entity by building processing and refining facility. Smelter activities can be considered to have higher complexity than mining due to involving more type of main equipment, type of main process, involving high temperature, more type of material to be handle, and deals with more environment aspects. The complexity causes more and new risks to be managed in the smelter plant compared with mining, especially the operational risks which classified into operation, safety, and environment category in PT Silo.